2-Methoxy-6-(6-methyl-1H-benzimidazol-2-yl)phenol - Naser Eltaher Eltayeb; Siang Guan Teoh; Ching Kheng Quah; Hoong-Kun Fun; Rohana Adnan (Acta Crystallographica Section E, 2009)
In the title molecule, C15H14N2O2, the substituted benzene ring forms a dihedral angle of 4.15 (1)° with the benzimidazole ring system. An intramolecular O—H...N hydrogen bond generates an S(6) ring motif. In the solid state, molecules are linked into chains along the [001] via intermolecular bifurcated N—H...(O,O) hydrogen bonds, which generate R12(5) ring motifs. The crystal packing is also consolidated by C—H...π interactions, and π–π stacking interactions between the imidazole and substituted benzene rings [centroid–centroid distance = 3.5746 (13) Å]. The methyl group attached to the benzimidazole ring system is disordered over two positions with occupancies of 0.587 (6) and 0.413 (6), suggesting 180° rotational disorder for the benzimidazole group.